Strategi Pengembangan Daya Tarik Wisata Alam Sanghyang Kenit Desa Rajamandala Kulon Bandung Barat - Emron Edison; Merdiana Hasanah Kurnia; Septy Indrianty (Tourism Scientific Journal, 2020)
The research was conducted in Rajamandala Kulon Village, west bandung Regency. It employed a qualitative research method by using SWOT Matrix. The source of interviewes were key informants from the Tourism Awareness Group (Pokdarwis) and the West Bandung Regency Tourism office. The results showed that Sanghyang kenit tourist destination has natural tourist attractions namely uniqueness, authenticity, scarcity and also it can foster enthusiasm and value for tourists. In other words, it qualifies as a tourist attraction. However, there are still several supporting factors that still need to be developed, both by the manager and the west Bandung regency tourism office. The development stage needs to be carried out based on the short, medium, and long term strategic plans.